The Effect of Reward System and Human Resource Development on Job Performance with Job Satisfaction as A Mediation on State Civil Apparatus in Human Resource Staff of The Indonesian National Police - Kalengkongan, Merlin Enjel; Soeling, Pantius Drahen (Journal of Law, Politic and Humanities, 2025)
The performance of State Civil Apparatus is influenced by many factors originating from the internal and external environments. This study highlights the reward system, human resource development, and job satisfaction as factors that influence the performance of State Civil Apparatus. This study aims to analyze the influence of the reward system and human resource development on job performance with job satisfaction as a mediation in the State Civil Apparatus in the National Police. This study will only highlight the assessment of State Civil Apparatus in the Police Human Resources Staff. The sampling technique used in this study was total sampling, so the sample of this study also totaled 131 people. This study uses a post-positivist paradigm. This study adopts Structural Equation Modeling in the form of Partial Least Square (SEM-PLS) using Smart PLS software. This study concludes that (1) the reward system has a positive effect on job performance (2) human resource development has a positive effect on job performance (3) job satisfaction has a positive effect on job performance, (4) the reward system has a positive effect on job satisfaction, (5) human resource development has a positive effect on job satisfaction, (6) the reward system has a positive effect on job performance through job satisfaction as a mediator, and (7) human resource development has a positive influence on job performance through job satisfaction as a mediator.